The use of stories and cartoons for teaching systemic dynamic ideas in children's and business arena - SAMUEL PRIETO MEJÍA; ZUANY LUZ PABA ARGOTE (Universidad del Magdalena, 2013)
This report pretend to jut out jut out the works that are doing several North American authors (principally Linda Booth Sweeney and David Hutchen, for treat of give Dynamic Systemic to the Childs' and the managerial public with the use of stories and caricature. The teaching of the concepts and ideas' transmition since a lot time are doing easier with the use of metaphor, parable or stories, this due that whit this tools, the persons aren't felling attacking, It's bigger remembering and the vocabulary that is used it isn't large that to do its understanding faster and its reach to a big public. Childs' literature have stories that can being used to transmit dynamics systemic way to the children how to explain "Linda Booth Sweeney" in her book "When a Butterfly Sneezes", where she shows twelve (12) north american stories that are using how tool to transmit Dynamics Systemic ideas in a simple way. Other important authors that used stories supporting by caricatures to transmit Dynamic systemic ideas and the organizational learning in the managerial ambit, is David Hutchens, who has published recently "Learning Fables Series", five illustrated book and other tools using like transparency, pocked book that are using as help to assessor and lecturer. Finally, we try motivatd the use of stories and caricature tools to transmit Dynamic System ideas in spanish